1992
DOI: 10.1002/iroh.19920770213
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐sea Environmental Disturbance and Recovery Potential

Abstract: Mining the abyssal seafloor for manganese nodules will destroy the hard substrate and it will severely disturb the seabed and the benthic soft substrate community. Recolonization will occur from unmined areas. Reestablishment of a community similar to that originally present is, however, not possible, since the nodules will be removed and epigrowth on hard substrates is thereby precluded. Small scale experiments using azoic sediment in trays exposed to ambient deep-sea conditions, may not be appropriate models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…This indicates that increased faunal density, on either side of the test site (Figure 3), immediately after the disturbance was a temporary phase caused by human interference. This supports the earlier finding of Thiel (1992) and others that physical disturbance, due to the sediment disturber have a long-term effect on sedimentation processes and the associated benthic fauna. Although, the heavy particles of the disturbed sediment plume might settle immediately, the fine particles may remain suspended in the bottom water (sediment-water interface) for a longer duration and may take a longer time for settling.…”
Section: Restoration Of Macrofauna After Disturbance In Cibsupporting
confidence: 90%
“…This indicates that increased faunal density, on either side of the test site (Figure 3), immediately after the disturbance was a temporary phase caused by human interference. This supports the earlier finding of Thiel (1992) and others that physical disturbance, due to the sediment disturber have a long-term effect on sedimentation processes and the associated benthic fauna. Although, the heavy particles of the disturbed sediment plume might settle immediately, the fine particles may remain suspended in the bottom water (sediment-water interface) for a longer duration and may take a longer time for settling.…”
Section: Restoration Of Macrofauna After Disturbance In Cibsupporting
confidence: 90%
“…Such experiments have included the V.S. Deep Ocean Mining Environmental Study (DOMES, see OZTURGUT et al, 1981) and the German large-scale Disturbance and recolonisation Experiment (DISCOL, see THIEL, 1992;THIEL et al, 1992THIEL et al, ,1993; THIEL and SCHRIE-VER, 1990). All these experiments have shown that dragging equipment across the deep-sea bed produces a large sediment plume.…”
Section: Potential Effects Of Fishing On Lophelia Pertusamentioning
confidence: 99%
“…This plume has a much wider area of impact than the area directly affected by towed equipment. The immediate effects of increased sedimentation in the vicinity of such operations is a decrease in the diversity of the fauna inhabiting the benthos, which may take years to recover (THIEL, 1992;THIEL et al, 1992THIEL et al, , 1993THIEL and SCHRIEVER, 1992). Benthic organisms are simply smothered, as resuspended sediment settles, or their feeding and respiratory structures are clogged.…”
Section: Potential Effects Of Fishing On Lophelia Pertusamentioning
confidence: 99%
See 1 more Smart Citation
“…Responsible approach to developing seafloor resources, including the polymetallic nodules, requires that potential effects, particularly the adverse ones, of such an activity for the bottom habitat and its communities be realised, assessed and minimised (Berge et al 1991;Jumars 1981;National Research Council 1984;Ozturgut et al 1978;Thiel 1992;Thiel et al 1992Thiel et al , 1998. At the present stage of preparations to commercial mining, the major actors (formerly termed the "pioneer investors" and currently known as the ISA contractors) are aware that they will be obliged to assess environmental consequences of mining, that is changes to the abiotic environment (bottom sediment and water column) and to the benthic and pelagic biota, resulting from mining activities.…”
Section: Prologuementioning
confidence: 99%